Colonizing the atmosphere: a common concern without climate justice law? - Susana Borràs (Journal of Political Ecology, 2019)
In the new 'Age of the Anthropocene', the Earth's atmosphere, like other elements of Nature, is rapidly being colonized by a minority of the world's population, at no cost, threatening the security of all humanity and the stability of the planet. The development processes of the great emitters of greenhouse gases have transferred social and environmental costs to all the world population, especially the most impoverished ones. This article is a critical analysis of how the legal climate change regime continues to legitimize the onslaught on the atmosphere. It reflects on the need to move to a new "climate justice law", characterized by responsibilities and obligations centered on the prevention, repair, restoration and treatment of damage and related risks linked to climate change, while protecting human rights and the atmosphere, as a common interest of humanity and the Earth.